2005
DOI: 10.1681/asn.2004110961
|View full text |Cite
|
Sign up to set email alerts
|

Acute-Phase Markers of Inflammation and Glomerular Structure in Patients with Type 2 Diabetes

Abstract: Type 2 diabetes is frequently associated with an inflammatory status; the relationships between low-grade inflammation and diabetic nephropathy are still unclear. The aim of this study was to evaluate the relationships between acute-phase markers of inflammation, glomerular structure, and albumin excretion rate (AER) in type 2 diabetes. In 74 patients with type 2 diabetes (23 normoalbuminuric, 30 microalbuminuric, and 21 proteinuric) fibrinogen, serum amyloid A protein (SAA), C-reactive protein (CRP), and IL-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
92
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(97 citation statements)
references
References 27 publications
4
92
0
1
Order By: Relevance
“…Several clinical and experimental studies have shown that a variety of inflammatory molecules, such as CRP, IL-6, and monocyte chemoattractant protein-1, are involved in the setting of diabetic nephropathy (27,28). In addition, studies show that CRP is not only a prototypic marker of inflammation but may directly influence CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical and experimental studies have shown that a variety of inflammatory molecules, such as CRP, IL-6, and monocyte chemoattractant protein-1, are involved in the setting of diabetic nephropathy (27,28). In addition, studies show that CRP is not only a prototypic marker of inflammation but may directly influence CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported AII-induced LIF and IL-6 gene expression in different cell types [49,52,53,54]. Importantly, it has been shown that increased systemic [18] and renal [55] expression of IL-6 is associated with diabetic nephropathy. Thus, the involvement of the IL-6 family of cytokines in mediating adverse cardiovascular [49] and renal [18, 55] outcomes appears well documented.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, it has been shown that increased systemic [18] and renal [55] expression of IL-6 is associated with diabetic nephropathy. Thus, the involvement of the IL-6 family of cytokines in mediating adverse cardiovascular [49] and renal [18, 55] outcomes appears well documented. HG by itself increased LIF mRNA levels 2.71 ± 0.35-fold over NG (p < 0.001; fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been suggested that inflammation plays an important role in the pathogenesis of diabetic nephropathy [34]. It is known that among inflammatory cytokines, IL-1, IL-6 and TNF-α are relevant for the development of diabetic nephropathy [35].…”
Section: Discussionmentioning
confidence: 99%